PEMBELAJARAN PROBLEM BASE LEARNING BERBASIS ANIMASI UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Mukhlis Mukhlis; Arusman Arusman (Lantanida Journal, 2020)
This animation-based PBL model research was conducted at MAN 4 Pidie Jaya, the research subjects were 34 class XI students. The research objective was to determine the increase in CBC and student response. This type of research is a quasi-experimental design with a pretest and posttest one group design, involving 1 (one) study group that is given an animation-based PBL learning model. Processing of research results using the T-test and N-Gain test. The results showed the mean scores for the initial and final CBC tests were 48.50 and 73.25. The t-test value of the statistical test t = 7.02 and tt = 1.70, so that t> tt, learning animation-based PBL models on Basic Law and Chemical Computing has an effect on students' CBC skills. The average value of the Gain and N-Gain test for the CBC ability of students was 24.75 and 0.48 or 48% were in the "medium" category. It can be concluded that learning PBL model based on animation on Basic Law Material and Chemical Calculations can improve students' CBC skills. The response of students obtained an average value of strongly agree and agree of 18.71% and 70%. The results of the students' responses showed that students liked learning through an animation-based PBL model.